Supergirl's family vacation - Snider, Brandon T. (DC Comics, 2026)
"Pre-teen Kara Zor-El is an excellent superhero. She always saves the day (and gets her homework in on time). But all anyone ever notices is her famous cousin Clark, who gets all the credit even though Kara's the one who captured Lex Luthor himself! Sigh. If only the people of Metropolis could see her greatness. Kara has an idea: summer's coming, and she wants to visit Argo, a floating city in space where the last survivors of Krypton live. These are her people, and, since Clark grew up on Earth, she can teach him a thing or two for once. It's the perfect plan! And it gets even better when Lois invites along Kara's best friend Natasha."--